A review of processing of Cu/C base plate composites for interfacial control and improved properties. (29th January 2020) - Silvain, Jean-François; Heintz, Jean-Marc; Veillere, Amélie; Constantin, Loic; Lu, Yong Feng
Abstract: The increase in both power and packing densities in power electronic devices has led to an increase in the market demand for effective heat-dissipating materials with a high thermal conductivity and thermal expansion coefficient compatible with chip materials while still ensuring the reliability of the power modules. Metal matrix composites, especially copper matrix composites, containing carbon fibers, carbon nanofibers, or diamond are considered very promising as the next generation of thermal-management materials in power electronic packages. These composites exhibit enhanced thermal properties, as compared to pure copper, combined with lower density. This paper presents powder metallurgy and hot uniaxial pressing fabrication techniques for copper/carbon composite materials which promise to be efficient heat-dissipation materials for power electronic modules. Thermal analyses clearly indicate that interfacial treatments are required in these composites to achieve high thermal and thermomechanical properties. Control of interfaces (through a novel reinforcement surface treatment, the addition of a carbide-forming element inside the copper powders, and processing methods), when selected carefully and processed properly, will form the right chemical/mechanical bonding between copper and carbon, enhancing all of the desired thermal and thermomechanical properties while minimizing the deleterious effects. This paper outlines a variety of methods and interfacial materials that achieve these goals.